Financial inclusion in Africa : improving it through fintech - Gamito, Susana Soares Ferreira (2018)
This paper is devoted to the study of financial inclusion in Africa, finding out how to measure it and how can we improve it through the use of fintech tools. The goal is to show that, using fintech, we can increase financial inclusion levels in the countries that needed the most in Africa by applying it in the dimensions that are mostly lacking from improvement. We begin by showing how to measure financial inclusion by applying it to the following dimensions: access, usage, price, equality and technology. Then we analysed the results to find out which are the dimensions that are most lacking from investment, comparing it to the top ten countries in terms of financial inclusion levels. It was shown that the African countries mostly needed investment in the dimensions of usage and equality. Lastly, we looked at those dimensions and recommended several different ways how we can improve it through fintech tools, showing also what some of the African countries have been doing so far in this regard. In here our recommendations were based on the use of interoperability, dematerialization, convergence, regulation and gamification.